Poster Presentation: A Project-Based Integrated Language Learning to Enhance Soft Skills of Japanese Language Learners - Lufi Wahidati; Mery Kharismawati (Chi'e: Journal of Japanese Learning and Teaching, 2023)
This study investigates how Japanese language students view group poster presentations as a project-based integrated language learning process. Japanese language students in higher education must possess both the hard and soft skills necessary for the workplace in the twenty-first century. Therefore, developing Japanese language learning methods is necessary to enhance both learners' soft skills and Japanese proficiency. The project-based learning (PjBL) approach was carried out through a project assigned in the Speaking course, namely in group poster presentations. This research investigated students' perceptions after implementing poster presentation activities to develop their soft skills. The research data were collected using questionnaires, interviews with selected students, and observations during the 8-week project. The results of this study show that the Japanese language students respond favourably to the implementation of the group poster presentation project. Poster presentation activities encourage the students to practice their four Japanese language skills (listening, speaking, reading, and writing) in realistic communication. At the same time, these group project activities help the students understand the value of interpersonal skills, project management, critical thinking and problem-solving, teamwork, and communication skills in completing a project. Keywords : Jurnal Pendidikan Bahasa Jepang Japanese Education JournalJapanese Language LearningJapanese Poster PresentationJapanese Vocational Education